Traveling Foreshocks and Transient Foreshock Phenomena. Issue 9 (25th September 2017) - Kajdič, P.; Blanco‐Cano, X.; Omidi, N.; Rojas‐Castillo, D.; Sibeck, D. G.; Billingham, L.
Abstract: We use the multispacecraft capabilities of the Cluster and Time History of Events and Macroscale Interactions during Substorms (THEMIS) missions to show that two types of foreshock may be detected in spacecraft data. One is the global foreshock that appears upstream of the Earth's quasi‐parallel bow shock under steady or variable interplanetary magnetic field. Another type is a traveling foreshock that is bounded by two rotational discontinuities in the interplanetary magnetic field and propagates along the bow shock. Foreshock compressional boundaries are found at the edges of both types of foreshock. We show that isolated foreshock cavities are a subset of the traveling foreshocks that form when two bounding rotational discontinuities are so close that the ultralow‐frequency waves do not develop in the region between them. We also report observations of a spontaneous hot flow anomaly inside a traveling foreshock. This means that other phenomena, such as foreshock cavitons, may also exist inside this type of foreshock. In the second part of this work we present statistical properties of phenomena related to the foreshock, namely, foreshock cavities, cavitons, spontaneous hot flow anomalies, and foreshock compressional boundaries. We show that spontaneous hot flow anomalies are the most depleted transient structures in terms of the B field and plasma density inside them and that the foreshock compressional boundaries and foreshock cavities are closely related structures. Plain Language Summary: Solar wind (SW) is ionized and magnetized gas propagating radially away from the Sun at supersonic speeds. When it encounters obstacles, such as our planet's magnetosphere, the SW is decelerated, deflected, and heated in a thin shock wave that stands in front of the obstacle. In case of Earth, its shock wave is supercritical, meaning that it reflects a portion of incoming SW particles (ions and electrons) that are reflected back sunward. If the conditions are right, these particles escape far upstream. The interaction of these reflected particles with the SW ones creates a region upstream of the Earth's bow shock called the foreshock region. In it the magnetic field is perturbed and different populations of ions inhabit it. Such region is called global foreshock of Earth. Here we describe another type of foreshock, which we call traveling foreshock, that occurs when the upstream interplanetary magnetic field (IMF) changes its orientation. This occurs since the IMF is composed of magnetic flux tubes that are not straight and are convected by the SW antisunward. In order to distinguish between the global and traveling foreshocks, multispacecraft observations are required. We discuss the relationships of different types of foreshocks with different foreshock phenomena. Key Points: Different types of foreshocks exist Relations between different types of foreshocks and foreshock transient phenomena All foreshock phenomena are put in a single scheme in solar foreshock coordinates